Traços da influência das filosofias de Platão e Aristóteles no desenvolvimento da matemática - Vieira, Demetrius Danton Arruda (2018)
The study of the history and philosophy of mathematics has become increasingly important for the improvement of the teaching-learning process of mathematics. This work seeks to contribute to this process by showing some relationships between mathematics and philosophy, and the importance of deepening in the history of mathematics studies and of relating history, philosophy and mathematics. It was presented as Plato's philosophy brought important contributions and influences to the development of mathematics and sought to relate the Platonic thinking to Euclid's mathematician doing as an example of inheritance of the teachings of Plato in the evolution of mathematics. In contrast to the Platonic philosophy, Aristotle's philosophy was presented, which was against his master's theory by emphasizing empiricism and denying the existence of a World of Ideas. And, similarly, a relation between Archimedes' mathematical doing and Aristotelian thought was shown as an example of Aristotle's influence and contribution to the development of mathematics.